Taktik Pajak: Mengeksplorasi Hubungan Corporate Risk, Book Tax Differences, Tax Avoidance, dan Manajemen Laba - Muslim, Ahmad Yudasmara; Sari, Diana (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This study aims to explore the impact of corporate risk and the differences between book-based income and tax income (Book Tax Differences) on tax avoidance, considering the moderating role of earnings management. The research method used is quantitative with descriptive analysis. The study population includes manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2021. The sampling technique was carried out through purposive sampling with a sample that met the criteria of 64 companies. The data used are secondary data in the form of financial statements over three (3) years of observation, analyzed using Moderated Regression Analysis (MRA) with Eviews 10 Software. The research results show that corporate risk and book tax differences significantly affect tax avoidance. Earnings management has been proven to negatively moderate the impact of corporate risk and book tax differences on tax avoidance. The implication of these findings suggests that risk management strategies and financial reporting transparency must be improved to reduce tax avoidance practices while ensuring tax compliance in an increasingly complex business environment.